2022
DOI: 10.1039/d1qm01285a
|View full text |Cite|
|
Sign up to set email alerts
|

Controlled chemical assembly of enzymes in cell lysate enabled by genetic-encoded nonstandard amino acids

Abstract: Enzyme proteins are nanometer-sized molecules with a three-dimensional structure that can be manipulated and assembled into highly ordered nanostructures, which allows access to advanced biological materials. Here, genetically-encoded nonstandard amino...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 79 publications
0
4
0
Order By: Relevance
“…Based on our previous studies, the mutant sites for AKR were identified as 130S, 162Q, 189Q, and 232W, and these sites were 104A, 125I, 155Y, 199P, and 204A for ADH. [18,23] The selection principles for mutation sites are as follows. 1) far from the active center; 2) less impact on the protein structure, considering similar group size or electronegativity; 3) located on the surface of a protein.…”
Section: Construction Of Fused Enzymes and Their Mutantsmentioning
confidence: 99%
“…Based on our previous studies, the mutant sites for AKR were identified as 130S, 162Q, 189Q, and 232W, and these sites were 104A, 125I, 155Y, 199P, and 204A for ADH. [18,23] The selection principles for mutation sites are as follows. 1) far from the active center; 2) less impact on the protein structure, considering similar group size or electronegativity; 3) located on the surface of a protein.…”
Section: Construction Of Fused Enzymes and Their Mutantsmentioning
confidence: 99%
“…In the biocatalytic asymmetric reduction of aryl alkyl ketones 93 the reductases have to cope with a wide variety of substituents in the aromatic ring, both electron-donating ( e.g. alkyl, alkoxy, amine), and electron-withdrawing ( e.g.…”
Section: Scope In the Enantioselective Synthesis Of Chiral Alcoholsmentioning
confidence: 99%
“…Here, if the insertion sites of NSAAs are rationally designed in space (Fig. 19(C)), the protein rings can be obtained 209 and further used as protein-based biomaterials for drug delivery or directly as clinical protein.…”
Section: Bio-orthogonal Immobilisation Mediated By Non-standard Amino...mentioning
confidence: 99%